Controlled Radical Polymerization Using a Novel Symmetrical Selenium RAFT Agent. Issue 17 (28th July 2014) - Botha, Carlo; Weber, Wolfgang; Pfukwa, Helen; Pasch, Harald
<x xml:space="preserve">Abstract</x> A novel symmetrical selenium‐based reversible addition‐fragmentation chain transfer (RAFT) agent, Se, Se'‐dibenzyl carbonodiselenothioate (Se‐RAFT), is synthesized and used in the RAFT polymerization of styrene. The results obtained show that the Se‐RAFT agent is involved in the polymerization of styrene, as evidenced by narrow molar‐mass distributions (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh177nh7xg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M¯w</alternatives>/<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh177nh7wx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M¯n</alternatives> < 1.6) and the incorporation of the Se‐RAFT moiety into the resultant polymer. The latter is confirmed by aminolysis, NMR spectroscopy, size‐exclusion chromatography (SEC) and UV spectroscopy. This work provides detailed insight into the Se‐RAFT polymerization mechanism. The Se‐RAFT agent is unique in that the stabilizing and leaving groups are identical. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>